The Concept of Suhrawardi’s Hudhuri Epistemology and Its Relevance to the Contemporary Challenges - Nur Hadi Ihsan; Martin Putra Perdana; Yongki Sutoyo (Dialogia, 2022)
Suhrawardi was a philosopher and a Sufi who robustly influenced the development of the sciences. With his philosophy of illumination (Hikmah al-Ishraq), he proposed the concept of hudhuri epistemology by which he fought against the domination of rationalistic and skeptical peripatetic epistemology that ultimately negated all forms of metaphysics. This paper aims to reveal the concept of Suhrawardi's epistemology, his anxiety and criticism of the validity problem of peripatetic philosophy, and the role of hudhuri's epistemology in responding to contemporary scientific challenges. This work is library research using documentary techniques to collect the necessary data. The collected data were analyzed utilizing the descriptive-analytical method. This study finds that the concept of hudhuri epistemology proposed by Suhrawardi presents the view that metaphysics is a dimension that cannot be separated from epistemology and can be rationalized. Furthermore, the metaphysical concept of faith, according to Suhrawardi, can be used as a solid philosophical foundation. Thus, with this hudhuri epistemology, the human senses and logical thinking limits can be transcended. Even with it, humans can acquire not only 'experience' or 'concepts' about reality, but they can also discover the nature of reality.